Subfoveal Choroidal Thickness After Femtosecond Laser-Assisted Cataract Surgery for Age-Related Cataracts - Chen, Wan; Chen, Hui; Mi, Lan; Li, Jing; Lin, Haotian; Chen, Weirong (Frontiers in Medicine, 2022)
Purpose: To compare the effects of femtosecond laser-assisted cataract surgery (FLACS) and conventional phacoemulsification surgery (CPS) on subfoveal choroidal thickness (SFCT) in patients with age-related cataracts. Methods: In this prospective consecutive study, 26 patients (26 eyes) with age-related cataracts without previous ocular surgery or other ocular diseases who had FLACS were included as the study group. Twenty-six age-matched patients (26 eyes) who underwent CPS in the same period were also included as the control group. The SFCT and the foveal retinal thickness (FRT) were measured at baseline and at 1 day (D1), 7 days (D7), 1 month (M1), and 3 months (M3) postoperatively by spectral-domain optical coherence tomography. Aqueous flare was also measured with a laser flare meter. Results: The mean SFCTs of the FLACS group at baseline and at D1, D7, M1, and M3 were 185.2, 174.3, 184.2, 180.8, and 184.1 µm, respectively. A Bonferroni posttest showed that the choroid became thinner on postoperative D1 (P = 0.006). The measurements at 1 week, 1 month, and 3 months postoperatively showed no significant differences in the SFCTs compared with that at baseline (P = 0.66, P = 0.22, and P = 0.53, respectively). A different trend was observed in the CPS group. The choroid became thicker by the 3-month postoperative measurement, as follows: 1 day (P = 0.28), 1 week (P = 0.016), 1 month (P = 0.020), and 3 months (P <0.001). Conclusion: The mean SFCT significantly and temporarily decreased following FLACS. In contrast, an increased SFCT was observed following CPS.